PERAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI DALAM MENANGKAL RADIKALISME DI INDONESIA - Pauzi (AL-KABIR: Jurnal Program Studi Pendidikan Agama Islam, 2023)
This research aims to provide deeper insight into the role of Islamic religious education in higher education in counteracting radicalism in Indonesia. This research uses a qualitative approach. This type of research is library research with library data collection methods, reading, recording, and processing research materials called library research or often also called library studies. The results of this study for Islamic religious education in higher education have an important role in shaping a correct, critical, and inclusive understanding of moderate and tolerant Islamic teachings. The Islamic religious education curriculum in higher education must be designed with attention to inclusiveness, critical thinking, national values, and tolerance. Lecturers have an important role in guiding students, providing moral examples, and facilitating open discussions on issues of radicalism. Students have an important contribution as agents of change in counteracting radicalism. In conclusion, Islamic religious education in higher education plays an important role in counteracting radicalism in Indonesia through an approach that is accurate, inclusive, critical, and based on national values and tolerance.